Measuring Interstellar Carbon Abundance via 158 μm [C ii] Absorption with SOFIA—A Potential Detection and Proof-of-concept for Depletion Studies with Future Far-IR Facilities - Christopher J. R. Clark; Julia. C. Roman-Duval; Suzanne C. Madden; Marc Mertens; Claire E. Murray; Jürgen Stutzki; Elizabeth Tarantino; Kirill Tchernyshyov (The Astronomical Journal)
Carbon plays key roles in the interstellar medium (ISM)—as a constituent of dust, as the carrier of the dominant far-infrared (FIR) cooling line, and as a component of various important molecules. But despite this, there are very few measurements of the abundance and depletion of carbon in the diffuse ISM. As with other elements, these measurements are traditionally performed in the ultraviolet. But for carbon, such measurements are extremely difficult, and fewer than 20 have been reported in the literature to date. Here, we present a novel method of measuring the abundance and depletion of carbon in the diffuse ISM: by observing absorption of the 158 μ m [C ii ] line in the FIR. We present a catalog of 432 candidate sightlines that use bright nearby galaxies as background sources, and predict the [C ii ] absorption expected toward each. We conducted a pilot study using SOFIA, targeting sightlines toward the galaxies IC 342 and Circinus. We report a potential detection of Galactic [C ii ] absorption along the IC 342 sightline, although it requires disentangling [C ii ] emission from IC 342 itself. The Circinus sightline had an insufficiently stable instrumental baseline to allow a detection. This SOFIA study informs the prospects for [C ii ] absorption measurements with future facilities. To that end, we explore the potential for four proposed future FIR telescopes—PRIMA, FIRSST, SALTUS, and Origins—to detect [C ii ] absorption. We find that all four facilities would be able to detect [C ii ] absorption along a significant number of sightlines.